Diet Quality of Chilean Schoolchildren: How Is It Linked to Adherence to Dietary Guidelines? - Pizarro-Quevedo, T (Public Library of Science, 2025)
Introduction In Chile, the prevalence of overweight among schoolchildren over the age of 5 is approximately 50%, one of the highest in the Americas region. This is largely influenced by the presence of inadequate food environments, characterized by limited access to healthy foods and a high availability of highly processed foods (HPF). This study analyzes food consumption in Chilean schoolchildren and the association of this with the Chilean Dietary Guidelines Based on Foods (DGBF) and the HPF consumption. Material and methods The sample (1,094 schoolchildren) was obtained from the baseline of the FONDEF IT18I0016 project, in Santiago-Chile. Anthropometry and socioeconomic data were measured. Dietary intake was assessed using a validated semi-quantitative frequency survey featuring images of food groups aligned with DGBF, as well as HPF. All data were collected by trained professional nutritionists. Associations between dependent and independent variables, and potential confounding factors were calculated using logistic regression models with stepwise backward/forward. A p < 0.05 was accepted as significant, using Stata 16.0. Results Most of the students (54.1%) were with malnutrition by excess and 20.0% exhibited abdominal obesity. Twenty percent of the students met the recommended intake for DGBF (fruits, vegetables, fish, milk and dairy products, legumes, water) and less than 5% did not consume any HPF. Consuming some sub-groups of HPF in moderate quantities (either no consumption or occasional consumption) increases the likelihood of meeting DGBF: candies and sweets (OR: 0.72; p = 0.04), pies with or without filling (OR: 0.63; p = 0.01), and salted snacks (OR: 0.67; p = 0.02). Conclusion Our results contribute to reaffirm the need to enhance healthy food consumption among schoolchildren and to discourage the intake of HPF, particularly focusing on specific sub-groups of HPF that may increase the risk of displacing the consumption of food groups recommended by the DGBF. © 2025 Pinheiro Fernandes et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.